Ethical aspects of the COVID-19 crisis: How to deal with an overwhelming shortage of acute beds. Issue 3 (April 2020) - Vincent, Jean-Louis; Creteur, Jacques
The current outbreak of SARS-CoV-2 has and continues to put huge pressure on intensive care units (ICUs) worldwide. Many patients with COVID-19 require some form of respiratory support and often have prolonged ICU stays, which results in a critical shortage of ICU beds. It is therefore not always physically possible to treat all the patients who require intensive care, raising major ethical dilemmas related to which patients should benefit from the limited resources and which should not. Here we consider some of the approaches to the acute shortages seen during this and other epidemics, including some guidelines for triaging ICU admissions and treatments.